PENGARUH HIPERKOAGULASI TERHADAP MORTALITAS ASTROSITOMA PADA PEMANTAUAN 12 BULAN - Among Wibowo; Tiara Aninditha; Henry Riyanto Sofyan; Rini Andriani (PERDOSNI, 2019)
EFFECT OF HYPERCOAGULABILITY TO ASTROCYTOMA MORTALITY WITHIN 12-MONTHS OF FOLLOW UPABSTRACTIntroduction: Astrocytoma is the most common primary brain tumor. Hypercoagulable state is one of brain tumor complications which can cause vein thromboembolism (VTE). Vein thromboembolism incidence is increased in astrocytoma patients. Hypercoagulable state in astrocytoma could lower patient’s survival.Aim: To investigate the effect of hypercoagulable state on mortality within 12 months of follow up in astrocytoma patients.Methods: This study design was retrospective cohort. This research data was taken from medical records in Cipto Mangunkusumo General Hospital and Dharmais Cancer Center Hospital on December 2017-February 2018. The subjects were adult astrocytoma patients who had histopathology and hemostasis examination. The variables investigated in this study were gender, age, prothrombin time (PT), activated partial thromboplastin time (aPTT), and D-dimer. Data processed descriptively and analytically using SPSS ver. 20 for Windows.Results: There were 49 subjects in this research. Around 30 (61.2%) subjects were men and 20 (40.8%) subjects aged >50 years old. High grade glioma was found in 39 (79.6%) subjects and hypercoagulable state was found in 34 (69.4%) subjects. There were 20 subjects deceased in 12-month follow-up. Subjects with hypercoagulable state had relative risk (RR) of 3.97 more susceptible to die in 12-month follow-up compared to control (p=0.009).Discussion: Hypercoagulation was a mortality risk factor in 12-month follow-up in patients with astrocytoma.Keywords: Astrocytoma, hypercoagulation, mortality within 12-months of follow upABSTRAKPendahuluan: Astrositoma merupakan tumor otak primer yang paling sering ditemukan. Salah satu komplikasi dari tumor otak adalah keadaan hiperkoagulasi. Keadaan hiperkoagulasi dapat menyebabkan tromboemboli vena. Insiden tromboemboli vena meningkat pada astrositoma. Keadaan hiperkoagulasi pada astrositoma dapat menurunkan kesintasan atau meningkatkan mortalitas pada pasien astrositoma.Tujuan: Mengetahui pengaruh hiperkoagulasi pada mortalitas pasien astrositoma dalam 12 bulan pemantauan.Metode: Penelitian kohort retrospektif terhadap pasien tumor otak jenis astrositoma yang dirawat oleh Divisi Neuroonkologi di RSUPN Dr. Cipto Mangunkusumo (RSCM) dan RS Pusat Kanker Dharmais (RSKD) pada bulan Desember 2017 hingga Februari 2018. Sumber data adalah data sekunder berupa rekam medis pasien dewasa yang telah memiliki hasil pemeriksaan histopatologis dan hemostasis. Variabel yang diambil dalam penelitian ini adalah jenis kelamin, usia, prothrombin time (PT), activated partial thromboplastin time (aPTT), dan D-dimer. Data diolah secara deskriptif dan analitik bivariat menggunakan SPSS ver. 20 for Windows.Hasil: Terdapat 49 subjek dalam penelitian ini yang mayoritas (61,2%) laki-laki, berusia <50 tahun (59,2%), dan memiliki jenis high grade gliomas (75,8%). Sebagian besar subjek mengalami hiperkoagulasi (69,4%) dan dalam kondisi hidup (59,2%) pada 12 bulan pascaperawatan. Subjek dengan hiperkoagulasi memiliki risiko relatif (RR) 3,97 kali lebih rentan mengalami kematian setelah 12 bulan dibandingkan kontrol (p=0,009).Diskusi: Hiperkoagulasi merupakan salah satu faktor risiko kematian dalam 12 bulan pada pasien astrositoma.Kata kunci: Astrositoma, hiperkoagulasi, mortalitas 12 bulan